Sustainable Energy in China : The Closing Window of Opportunity - Berrah, Noureddine; Feng, Fei; Priddle, Roland; Wang, Leiping (Washington, DC : World Bank, 2012)
This report proposes the development of a coordinated and comprehensive national policy within the Energy Law that is presently under preparation based on four foundational themes: reducing energy growth below economic growth, making better use of national energy resources, safeguarding the environment, and making the energy system robust to withstand potential disruptions. It stresses that the policy measures and program to achieve sustainability will have to be the subject of careful consultation within government and extend to mobilizing China's civil society. The scope of and potential for fruitful international cooperation is also explored, but the detail must be worked out in a cooperative framework. The main body of the report is arranged in six chapters. The first examines what the projections say about the future of China's energy consumption and concludes that urgent action is needed to avoid locking the country into an unsustainable energy development path. Chapter two evaluates end-use efficiency and finds that a less energy-intensive path can be founded on the most advanced technologies. The third chapter examines the damaging environmental impacts of the huge prospective energy growth, which dictate the need for a less-intensive path, a larger share of clean energy sources, and dramatically more clean coal. Chapter four assesses security of energy supply and proposes means to improve it and ensure the safety of national energy supply sources and networks. The fifth chapter emphasizes getting right the pricing fundamentals of the sector. The last chapter draws conclusions from the first five on matters requiring urgent policy attention and proposes development of a coordinated and comprehensive national policy for energy sustainability.